METODE ANALISIS PERBANDINGAN TULANGAN STEK DAN TULANGAN MENERUS KOLOM PADA PROYEK PASAR LEGI PARAKAN TEMANGGUNG PT. HUTAMA KARYA (Persero). - , ARIEF WIRAGUNA, Agus Kurniawan, ST.,MT.,Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Column is a vertical compression member that serves to support the load of the roof. The installment of reinforcing steel bar is done paralel with steel of pilecap. At the beginning of the Pasar Legi Parakan project construction, the zero point floor elevation was not yet known, so the height of the column reinforcement could not been determined. The method of overstek reinforcement was used to speed up pilecap casting, while a review design has been done. The methods of overstek reinforcement done by installing reinforcement along one meter plus high of pilecap, whereas for continuous reinforcement normally fitted with the appropriate distance between the floor height. While,if there are paralel work are in same time, then the overstek reinforcement method can be used as an alternative to speed up the completion of the construction below it. From the calculation it is known that continuous reinforcement is more efficient in terms of cost and time, the aspect of cuttings reinforcement, as reinforcement could be balance any overstek in field, so that construction could continue running.